Everyday moral issues experienced by managers - Waters, James A. (Journal of business ethics, 1986)
Based on the results of open ended interviews with managers in a variety of organizational positions, moral questions encountered in everyday managerial life are described. These involve transactions with employees, peers and superiors, customers, suppliers and other stakeholders. It is suggested that managers identify transactions as involving personal moral concern when they believe that a moral standard has a bearing on the situation and when they experience themselves as having the power to affect the transaction. This is the first in a research series of three papers.